Propedeutic styles for the formative assessment in the accounting discipline: Learning outcomes - Llanos Ceballos, Adolfo León (2022)
This review article presents an analysis of the propaedeutic possibilities to evaluate in a model for learning outcomes; additionally, it recognizes that teaching, learning, and evaluation actions are part of the same unit. Likewise, the learning assessment criteria in the accounting discipline must be constructed in relation to the learning conception and the type of addressed competence (basic, generic, specific); a highly complex activity as evidenced by the systematization of the practice. In its final part, after establishing an example of evaluation in the subject of comprehension and creation of academic texts corresponding to the general training of the public accountant, the academic discussion is developed on the taxonomies that the university could assume in the construction, deployment and monitoring of a route to evaluate in the sense of the result; therefore, a taxonomy proposal is formulated for the field of specific or technical competences of the discipline under study.